Investigation on the thermal response of full-scale PHC energy pile and ground temperature in multi-layer strata. (October 2018) - Guo, Yimu; Zhang, Guozhu; Liu, Songyu
Highlights: In-situ TRT was conducted on a PHC pipe pile installed in multi-layered ground. The thermal conductivity of ground was compared to results from laboratory tests. The heat transfer process in pile and layered ground was analyzed. Abstract: A thermal response test (TRT) was conducted on a full-scale precast high strength concrete (PHC) pipe pile installed in multi-layered ground, in order to investigate the thermal response of the pile and soils in inhomogeneous ground. The thermal properties of each layer were tested in the laboratory and compared to the estimation from the TRT. The ground temperature evolution was monitored using 4 boreholes around the pile, and the pile temperature distribution was captured from transducers prefabricated in the pile wall. The system thermal conductivity estimated from TRT results was 2.11 W/(m K) which is about 2 times that from the lab test (1.15–1.71 W/(m K)). The comparison with other TRTs suggests that fitting time and heating power may influence the estimated results. The ground temperature response varied along the depth. Comparing the layers, more conductive soil was cooler near the pile but warmer at a distance. Up to 23% difference of temperature increment (1.1 °C) was found. The pile temperature was less influenced by soil stratification but was evidently affected by end effects, which caused a maximum difference of 16% (3.2 °C) from the average temperature increment. The average ground and pile temperature increased by 1.1 °C and 1.5 °C respectively at 37 days after heating. This suggests that an accumulated temperature increase could happen in a cooling-dominated district.